Almitrine Infusion in Severe Acute Respiratory Syndrome Coronavirus 2-Induced Acute Respiratory Distress Syndrome: A Single-Center Observational Study*. Issue 2 (22nd October 2020) - Caplan, Morgan; Goutay, Julien; Bignon, Anne; Jaillette, Emmanuelle; Favory, Raphael; Mathieu, Daniel; Parmentier-Decrucq, Erika; Poissy, Julien; Duburcq, Thibault
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Treating acute respiratory failure in patients with coronavirus disease 2019 is challenging due to the lack of knowledge of the underlying pathophysiology. Hypoxemia may be explained in part by the loss of hypoxic pulmonary vasoconstriction. The present study assessed the effect of almitrine, a selective pulmonary vasoconstrictor, on arterial oxygenation in severe acute respiratory syndrome coronavirus 2-induced acute respiratory distress syndrome. Design: Single-center retrospective observational study. Setting: ICU of Lille Teaching Hospital, France, from February 27, 2020, to April 14, 2020. Patients: Patients with coronavirus disease 2019 pneumonia confirmed by positive reverse transcriptase-polymerase chain reaction for severe acute respiratory syndrome-coronavirus 2 and acute respiratory distress syndrome according to Berlin definition. Data focused on clinicobiological features, ventilator settings, therapeutics, outcomes, and almitrine-related adverse events. Interventions: Almitrine was considered in patients with severe hypoxemia (Pao 2 /Fio 2 ratio < 150 mm Hg) in addition to the recommended therapies, at an hourly IV delivery of 10 μg/kg/min. Comparative blood gases were done before starting almitrine trial and immediately after the end of the infusion. A positive response to almitrine was defined by an increase of Pao 2 /Fio 2 ratio greater than or equal to 20% at the end of the infusion. Measurements and Main Results: A total of 169 patients were enrolled. Thirty-two patients with acute respiratory distress syndrome received an almitrine infusion trial. In most cases, almitrine was infused in combination with inhaled nitric oxide (75%). Twenty-one patients (66%) were responders. The median Pao 2 /Fio 2 ratio improvement was 39% (9–93%) and differs significantly between the responders and nonresponders (67% [39–131%] vs 6% [9–16%], respectively; p < 0.0001). The 28-day mortality rates were 47.6% and 63.6% ( p = 0.39) for the responders and nonresponders, respectively. Hemodynamic parameters remained similar before and after the trial, not suggesting acute cor pulmonale. Conclusions: Almitrine infusion improved oxygenation in severe acute respiratory syndrome coronavirus 2-induced acute respiratory distress syndrome without adverse effects. In a multistep clinical approach to manage severe hypoxemia in this population, almitrine could be an interesting therapeutic option to counteract the loss of hypoxic pulmonary vasoconstriction and redistribute blood flow away from shunting zones.